A Review: The Development Of Metamaterial Absorber - Md Ali, Siti Adlina; Abu, Maisarah; Zabri @ Suhaimi, Siti Normi (Penerbit UTHM, 2020)
A metamaterial is an artificial resonant structure that is designed to obtain specific characteristics which are not naturally occurring in nature. One of the applications is metamaterial absorber, which offers benefits over conventional absorbers. Metamaterials absorber is a structure that attenuates the energy in electromagnetic waves, soak up the incident energy, convert into heat and reduce the energy reflected back to the source. Various designs on metamaterial absorber have been investigated exhibiting different characteristics; single-band, multi-band, as well as broadband. Starting from thick and rigid substrates, followed by a thin and also flexible substrate materials are being considered. Perfect absorbency is achieved when the surface impedance of the structure equal to the free space impedance. Different methods in introducing the loss in an absorber; lumped resistor, resistive pattern and lossy dielectric. These unique characteristics of metamaterial absorber enable wide applications in various technologies.